A forma política do negacionismo: o caso da ciência brasileira pós-2018 - Vicente, William Augusto (Universidade Federal de São Carlos, 2023)
The aim of this term paper was to analyze how the phenomenon of negationism is constituted and manifested in Brazilian civil society, specifically in the political and academic fields, in order to understand possible consequences for the formation of the subjectivity of social beings and their alienation from reality. Negationism, understood as a historical element of humanity, can be classified as a form of manipulation of reality for the sake of an ideology. Through historical revisionism of the constitution of facts, operated by the manipulation of information and its means of communication, a distorted notion of truth is established, sustained by the stimulation of pleasures that may be frustrated by the conditions derived from the cultural organization of a given region. Thus, the subjectivity of the individual sensitized by malaise is a psychological state exploited by demagoguery, which seeks to introduce ideals through the stimulation of pleasure and modify the understanding of facts that are contrary to its objectives. In this way, various manifestations of a disinformative nature are manipulated in order to produce an effect of acceptance, as well as being disseminated by the most efficient means of communication, with a view to their breadth and speed of reach. As a result, several socio-political actions have been observed that are supported by negationist theories, as well as a project of alienation and hijacking of the subjectivity of the social being, which aim to maintain the precariousness of education and, in this way, prevent the formation of critical consciences capable of understanding the reality in which they exist.
The political form of negationism: the case of post-2018 brazilian science
Keywords: Sociedade civil; Negacionismo científico; Políticas públicas; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO